Review Theories of E-Learning - Alharbi, Omran; Alshammari, Yousef; AlMutairi, Awatif (Advances in Social Sciences Research Journal, 2022)
There are several theories, which can be adopted and integrated to investigate the adoption of technology from learners and instructors’ perceptions in education environment. However, little of research were conducted to provide a comprehensive review of these theories. This study will present a comprehensive review of the essential theories such as Theory of Reasoned Action (TRA), Theory of Planned Behaviour (TPB), Social Cognitive Theory (SCT), Diffusion of Innovations Theory (DIT), Motivational Model (MM) ,Model of Personal Computing Utilization (MPCU) ,Unified Theory of Acceptance and Use of Technology (UTAUT) Model Technology Acceptance Model (TAM). Also, this paper attempt to provide some justifications about why the TAM model has used in research more than others theories.